Combining Internal Carotid Artery Occlusion with Intermediate-Flow Bypass for Treating Large-Giant Cavernous Sinus Segment Aneurysms: Case Report and Review of Literature - Bhattarai, Robin; Chen, Chuan; Liang, Chao Feng; Huang, Teng Chao; Wang, Hui; Guo, Ying (Nepal Journal of Neuroscience, 2019)
We summarize the treatment effectiveness and experience of a patient who underwent internal carotid balloon occlusion combined with Intermediate-flow bypass as a treatment for large-giant cavernous sinus segment internalcarotid artery (CS ICA) aneurysms.A 62-year-old woman presented with a large aneurysm on the right side of the cavernoussinus with dizziness for about two years and Oculomot or nerve palsy. An extra cranial intracranial (EC-IC) Intermediate-flow by pass using a radial artery bypass graft (RABG) and proximal balloon occlusion of the Right ICA were performed. The patient experienced no new neurologic deficit after this treatment. Follow up radiologic evaluations using Computed Tomography Angiography revealed complete aneurysm occlusion.For patients with large-giant CS ICA aneurysms, treatment of ICA occlusion combined with Intermediate-flow superficial temporal artery-Radial artery-middle cerebralartery bypass surgery was an effective and safe surgical strategy.